2021
DOI: 10.1007/s11192-021-03987-y
|View full text |Cite
|
Sign up to set email alerts
|

Research ethics: a profile of retractions from world class universities

Abstract: This study aims to profile the scientific retractions published in journals indexed in the Web of Science database from 2010 to 2019, from researchers at the top 20 World Class Universities according to the Times Higher Education global ranking of 2020. Descriptive statistics, Pearson's correlation coefficient, and simple linear regression were used to analyze the data. Of the 330 analyzed retractions, Harvard University had the highest number of retractions and the main reason for retraction was data results.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 77 publications
(188 reference statements)
0
13
0
Order By: Relevance
“…There are growing frustrations with the lack of institutional action, response, or even communication with the Editors of journals when concerns arise (Marcus, 2020). Institutions must be made aware of the impact of retractions on their reputation, as well as develop policies on the matter of misconduct, and strictly enforce swift punitive actions when misconduct is identified-proactive engagement with the Editors of journals and avoidance of obstructing or delaying investigations is necessary (Lievore et al, 2021;Steen et al, 2013;Stern et al, 2014;Yi et al, 2019). Fake peer review, fake authorship, and even fake editors are a clue to the lengths researchers can go to in order to publish their work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are growing frustrations with the lack of institutional action, response, or even communication with the Editors of journals when concerns arise (Marcus, 2020). Institutions must be made aware of the impact of retractions on their reputation, as well as develop policies on the matter of misconduct, and strictly enforce swift punitive actions when misconduct is identified-proactive engagement with the Editors of journals and avoidance of obstructing or delaying investigations is necessary (Lievore et al, 2021;Steen et al, 2013;Stern et al, 2014;Yi et al, 2019). Fake peer review, fake authorship, and even fake editors are a clue to the lengths researchers can go to in order to publish their work.…”
Section: Discussionmentioning
confidence: 99%
“…Institutions must be made aware of the impact of retractions on their reputation, as well as develop policies on the matter of misconduct, and strictly enforce swift punitive actions when misconduct is identified-proactive engagement with the Editors of journals and avoidance of obstructing or delaying investigations is necessary (Lievore et al, 2021; Steen et al, 2013; Stern et al, 2014; Yi et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…When it comes to reasons for retractions, a considerable share is attributed to misconduct, especially to falsification, fabrication, plagiarism, in different fields, with smaller fractions for honest errors (Fang et al, 2012;Bozzo et al, 2017;Li et al, 2018;Ribeiro and Vasconcelos, 2018;Coudert, 2019;Christopher, 2022). A recent analysis of 330 retractions (2010)(2011)(2012)(2013)(2014)(2015)(2016)(2017)(2018)(2019) in journals indexed in the Web of Science database showed that 66.4% accounted for data results, including falsification, fabrication, and unreliable results (Lievore et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Retractions have increased in both number and prominence over the past 2 decades. 1 , 2 More recently, concerns have been raised about the number of retracted COVID-19 studies. 3 While these retractions may be due to greater external scrutiny of COVID-19 literature, little is known about the potential differences between retracted COVID-19 studies and studies on other topics.…”
Section: Introductionmentioning
confidence: 99%
“…Manuscript retractions represent attempts to officially withdraw published papers or posted preprints that contain errors, fraud, or other kinds of misconduct. Retractions have increased in both number and prominence over the past 2 decades . More recently, concerns have been raised about the number of retracted COVID-19 studies .…”
Section: Introductionmentioning
confidence: 99%